Telegram notice, March 31, 1942 - Western Union Telegraph Company (1942)
Notice that Max Bredig's (1902-1977) telegram could not be delivered to Margaret Lambie.
Keywords: Bredig, Max Albert, 1902-1977; Lambie, Margaret; Western Union Telegraph Company